CONSUMER PERCEPTION TOWARDS ONLINE ADVERTISEMENT - M.Saravanan 1 , Sajitha. S (International Research Journal of Engineering and Technology, 2016)
In recent years, the decline of the mass media and growth of internet and fragmented audience, online have forced advertisers, agencies and publishers to revise their thinking about delivering marketing message to consumers .Change in web technology and customer’s behaviour has in many cases, increasedopportunities to target advertising yet how to make the most effective use of the web as a channel for commerce and communications has proven to be more elusive. This paper investigates the implication of this shift for consumers and industry and the how, where and why of innovations in this field. Using this data, it also looks ahead to the future and how evolving concepts of relevance and utility for consumers will shape online advertising in the years to come .